Opsoclonus Myoclonus Ataxia Syndrome - Kunchapudi, SK; Kumar, P; Sabharwal, RK (Journal of Nepal Paediatric Society, 2015)
Opsoclonus myoclonus ataxia syndrome (OMAS) is a rare neurological disorder predominantly affecting young children and causing severe neurological disability. Its early identification and treatment is advocated. Here we report a two year old child presenting with abnormal movements and subsequently developed features of OMAS and responding favourably to Adrenocorticotropic hormone (ACTH). J Nepal Paediatr Soc 2015;35(1):70-72